Estimation of the future remnant liver function is a better tool to predict post-hepatectomy liver failure than platelet-based liver scores. Issue 12 (December 2017) - Chapelle, T.; Op de Beeck, B.; Driessen, A.; Roeyen, G.; Bracke, B.; Hartman, V.; Huyghe, I.; Morrison, S.; Ysebaert, D.; Francque, S.
Abstract: Introduction: Recently, there has been increasing interest in the preoperative prediction and prevention of post-hepatectomy liver failure (PHLF). This is a particular concern in colorectal liver metastases (CRLM), when surgery follows potentially hepatotoxic chemotherapy. Platelet-based liver scores (PBLS) such as APRI and FIB-4 are predictive of chemotherapy-associated liver injury (CALI) and PHLF. Estimation of the future liver remnant function (eFLRF) by combining 99m Tc-Mebrofenin Hepatobiliary Scintigraphy (HBS BSA ) with future liver remnant volume ratio (FLRV%), is predictive of PHLF and related mortality. We hypothesized that a HBS BSA based formula was a better predictor for PHLF than PBLS in chemotherapy-pretreated CRLM. Methods: Between 2012 and 2016, 140 patients underwent liver resection for CRLM following systemic therapy. HBS BSA, FLRV%, eFLRF and PBLS were calculated and compared for their value in predicting PHLF. Results: eFLRF and FLRV% had a better predictive value for PHLF than HBS BSA alone and APRI and FIB-4 (AUC = 0.800, 0.843 versus 0.652, 0.635 and 0.658 respectively). In a subgroup analysis (Oxaliplatin all, Oxaliplatin ≥ 6 cycles, Irinotecan all and Irinotecan ≥ 6 cycles), eFLRF was the only factor predictive for PHLF in all subgroups (all: p ≤ 0.05). Prediction of HBS BSA for chemotherapy associated steato-hepatitis (CASH) reached almost significance (p = 0.06). FIB-4 was predictive for sinusoidal obstruction syndrome (SOS) (p = 0.011). Only weak correlation was found between HBS BSA and PBLS. Conclusion: eFLRF is a better predictor of PHLF than PBLS or HBS BSA alone. PBLS seem to measure other aspects of liver function or damage than HBS BSA .